P66 GENDER–RELATED DIFFERENCES IN CLINICAL OUTCOMES AFTER EITHER SINGLE OR DOUBLE LEFT MAIN BIFURCATION STENTING. (18th May 2022) - Rigatelli, G; Zuin, M; Gianese, F; Osti, S; Bilato, C; Roncon, L
Abstract: Background: We sought to examine the impact of gender differences in clinical outcomes at 3 years also comparing the role of double versus single stenting approach for the treatment of coronary unprotected LM bifurcation lesions. Methods: We retrospectively analyzed both the procedural and medical data of patients referred to our hub center for complex LM bifurcation disease, treated using Cross–over provisional stenting, T or T–and–Protrusion (TAP), Culotte, and Nano–inverted–T (NIT) techniques between January1st, 2008 to May1st2018. The main outcome of the study was to evaluate the association between gender and target lesion failure (TLF) based on the different stenting technique used. Results: Five hundred and sixty–seven patients (251 females, mean age 70.0±10 years, mean Syntax score 31.6±6.3) were evaluated. Cross–over, T or TAP, culotte and NIT techniques were performed in 171 (30.1%), 61 (10.7%), 98(17.2%) and 237 (41.8%) patients, respectively with no differences in baseline and peri–procedural items among gender. At a mean follow–up of 37.1±10.8 months (range 22.1–39.3 moths), the overall TLF rate, cardiovascular mortality and stent thrombosis were 12.1%, 3.1% and 1.0%, respectively. Female gender was associated with an increased rate of major bleeding when treated with double stent strategy (p = 0.02). No gender difference in TLF was noted among gender, independently from the stenting approach used. Conclusions: Among patients with ULM bifurcation disease undergoing PCI, TLF rates were not different between genders at 3–year follow–up either using a single or double stent technique.